Pengaruh Fear of Missing Out (FoMO) di Media Sosial Terhadap Keputusan Pembelian Fashion Dengan Brand Image Sebagai Variabel Moderasi - Vincentia Indah Puspita Sari; Margareta Ernanda Rahardani (Universitas Proklamasi 45, 2026)
This study analyzes the influence of fear of missing out (FoMO) on purchase decisions. Brand image was used as a moderating variable. The method applied in this study is quantitative. The respondents used in this study were consumers who use social media and have purchased fashion products due to exposure to trends on social media. The sample used in this study was 180. The data collection technique used a questionnaire. The data were analyzed using SmartPLS 3.0. The results showed that FoMO has a positive influence on purchase decisions. The presence of brand image weakens the relationship between FoMO and purchase decisions.